Limit on Lorentz-invariance- and CPT-violating neutron spin interactions using a 3He-129Xe comagnetometer - Allmendinger, Fabian; Schmidt, Ulrich; Heil, W.; Karpuk, S.; Sobolev, Yu.; Tullney, K. (International journal of modern physics. Conference series, 2016)
We performed a search for a Lorentz-invariance- and CPT-violating coupling of the 3He and 129129129Xe nuclear spins to posited background fields. Our experimental approach is to measure the free precession of nuclear spin polarized 3He and 129129129Xe atoms using SQUIDs as detectors. As the laboratory reference frame rotates with respect to distant stars, we look for a sidereal modulation of the Larmor frequencies of the co-located spin samples. As a result we obtain an upper limit on the equatorial component of the background field b˜n⊥<8.4⋅10−34b̃⊥n<8.4⋅10−34<msubsup><mover accent="true">b̃</mover>⊥n</msubsup><8.4⋅10−34 GeV (68% C.L.). This experiment is currently the most precise test of spin anisotropy due to the excellent long spin-coherence time.